Towards an on-going formation program for the St. Joseph Sisters in Myanmar based on Van Kaam-Garvey’s formation field theory - Lim, Magdalene (Animo Repository, 2008)
This study was devoted to proposing an on-going formation program based on Van Kaam- Garvey's formation field theory for the finally professed Sisters of the Congregation of St. Joseph of the Apparition in the Myanmar Province. This proposal was made based on the perception of the Sisters from the present on-going formation program that was first studied. This was drawn from the documents; General Chapters and Guide Book for formation, and survey. For this reason fifty finally professed Sisters were chosen. Only twenty three Sisters from Myanmar and five Burmese Sisters from the Philippines responded to this research of documentary analysis and survey descriptive method. Documents were taken from the orientations based on the resolutions of the three consecutive General Chapters from 1989 to 2001 which served as the directions for the on-going formation of the Sisters. The SJA Guide Book for formation was one of the main directions used for formation. The perception of the Sisters' formation was categorized according to the polarities of Van Kaam-Garvey's formation field theory (Mystery, Intraformation, Interformation, Situational Formation, and World Formation) to find out how they were interrelated. The result of the study showed an imbalanced formation program according to Van Kaam- Garvery's formation field theory. According to Van Kaam-Garvey (1995), human/spiritual formation is a balanced development of a person's socio-cultural, vital, functional, transcendent levels and their proper unfolding of the person (Pg. 22). In this finding, intraformation was highly achieved. There was vii little emphasis on situational and world formation. Achievement was favored for only a few Sisters and duration for formation was not qualified. The conclusion was that the objectives of the on-going formation were not met especially the first objective of bringing about the growth of the persons at all levels. Therefore the human and spiritual growth of the Sisters was not fully achieved resulting in the revitalization of the Congregation not being actualized. In order to revitalize, the holistic, integrated, balanced and contextualized on-going formation is needed. Based on the conclusion, the proposal for the on-going formation was made. This was to integrate the formation field of Van Kaam modified by Garvey to the present on-going formation program in Myanmar.